Effects of primary care antimicrobial stewardship outreach on antibiotic use by general practice staff: pragmatic randomized controlled trial of the TARGET antibiotics workshop. (5th March 2018) - McNulty, Cliodna; Hawking, Meredith; Lecky, Donna; Jones, Leah; Owens, Rebecca; Charlett, André; Butler, Chris; Moore, Philippa; Francis, Nick
Abstract: Objectives: To determine whether local trainer-led TARGET antibiotic interactive workshops improve antibiotic dispensing in general practice. Methods: Using a McNulty–Zelen-design randomized controlled trial within three regions of England, 152 general practices were stratified by clinical commissioning group, antibiotic dispensing rate and practice patient list size, then randomly allocated to intervention (offered TARGET workshop that incorporated a presentation, reflection on antibiotic data, promotion of patient and general practice (GP) staff resources, clinical scenarios and action planning, 73 practices) or control (usual practice, 79 practices). The primary outcome measure was total oral antibiotic items dispensed/1000 patients for the year after the workshop (or pseudo-workshop date for controls), adjusted for the previous year's dispensing. Results: Thirty-six (51%) intervention practices (166 GPs, 51 nurses and 101 other staff) accepted a TARGET workshop invitation. In the ITT analysis total antibiotic dispensing was 2.7% lower in intervention practices (95% CI −5.5% to 1%, P  =   0.06) compared with controls. Dispensing in intervention practices was 4.4% lower for amoxicillin/ampicillin (95% CI 0.6%–8%, P  =   0.02); 5.6% lower for trimethoprim (95% CI 0.7%–10.2%, P  =   0.03); and a non-significant 7.1% higher for nitrofurantoin (95% CI −0.03 to 15%, P  =   0.06). The Complier Average Causal Effect (CACE) analysis, which estimates impact in those that comply with assigned intervention, indicated 6.1% (95% CI 0.2%–11.7%, P  =   0.04) lower total antibiotic dispensing in intervention practices and 11% (95% CI 1.6%–19.5%, P  =   0.02) lower trimethoprim dispensing. Conclusions: This study within usual service provision found that TARGET antibiotic workshops can help improve antibiotic use, and therefore should be considered as part of any national antimicrobial stewardship initiatives. Additional local facilitation will be needed to encourage all general practices to participate.